2009
DOI: 10.1002/adfm.200801515
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Hydrous Manganese Dioxide Nanowall Arrays with Large Lithium Ion Energy Storage Capacities

Abstract: Novel nanowall arrays of hydrous manganese dioxide MnO2 · 0.5H2O are deposited onto cathodic substrates by the potentiostatic method from a mixed aqueous solution of manganese acetate and sodium sulfate. The deposition is induced by a change of local pH resulting from electrolysis of H2O, and hierarchical mesoporous nanowall arrays are formed as a result of simultaneous precipitation of manganese hydroxide and release of hydrogen gas bubbles from the cathode. The morphology and lithium ion intercalation proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(109 citation statements)
references
References 55 publications
5
102
1
Order By: Relevance
“…It can be seen that the surface contains nanosized pores that are distributed uniformly on the surface. It has been reported that gas bubbles during electrodeposition can result in the mesoporous film formation [39]. Beside this effect, as seen in marked areas of Fig.…”
Section: Resultsmentioning
confidence: 92%
“…It can be seen that the surface contains nanosized pores that are distributed uniformly on the surface. It has been reported that gas bubbles during electrodeposition can result in the mesoporous film formation [39]. Beside this effect, as seen in marked areas of Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Most previous studies of electrochemical deposition of MnO 2 were based on anodic deposition via a positive potential-namely, the starting Mn 2+ species can be oxidized to Mn 4+ and deposited as MnO 2 [33,37,51]. However, there have been few reports focusing on the cathodic electrochemical deposition of MnO 2 at a negative potential because of the different growth mechanisms [47,52]. In this work, we established a facile and effective way for the simultaneous electrochemical reduction of GN and cathodic electrochemical deposition of MnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Since both Mn(OH) 2 and Al(OH) 3 formed by the reaction between Mn/Al salts and NH 4 OH have very low solubility in water, their precipitation occurs in aqueous solution. 15,[30][31][32][33][34][35][36] During this precipitation process, the precursors of composites were prepared through the hydrogen bonding between Mn(OH) 2 and Al(OH) 3 . Then, alumina-manganese oxide composite particles could be obtained after the calcination of precursor powders.…”
Section: Resultsmentioning
confidence: 99%